Nitric oxide- and nitric oxide donors-induced relaxation and its modulation by oxidative stress in piglet pulmonary arteries - López López, José Gustavo; Pérez Vizcaíno, Francisco; Cogolludo, Angel L.; Ibarra, Manuel; Zaragozá Harnáez, Francisco; Tamargo, Juan (My University, 2001)
1 Inhaled nitric oxide (iNO) is widely used in the treatment of pulmonary hypertension while inhaled NO donors have been suggested as an alternative therapy. The di erential susceptibility to inactivation by oxidative stress and oxyhaemoglobin of NO and two NO donors, sodium nitroprusside (SNP) and S-nitroso-N-acetyl-penicillamine (SNAP) were analysed in isolated endothelium-denuded pulmonary arteries from 2-week-old piglets stimulated with U46619. 2 NO, SNAP and SNP relaxed the arteries (pIC30=7.73+0.12, 7.26+0.17 and 6.43+0.13, respectively) but NO was not detected electrochemically in the bath after the addition of SNP and only at concentrations at which SNAP produced more than 50% relaxation. 3 The sGC inhibitor ODQ (1076 M) or the sarcoplasmic Ca2+-ATPase thapsigargin (261076 M) markedly inhibited the relaxation induced by NO, SNAP and SNP. 4 Addition of oxyhaemoglobin (361077 M) or diethyldithiocarbamate (1 mM) markedly inhibited NO- (pIC30=6.88+0.07 and 6.92+0.18, respectively), weakly inhibited SNAP- and had no e ect on SNP-induced relaxation. Xanthine oxidase (5 mu ml71 ) plus hypoxanthine (1074 M) markedly inhibited NO- (pIC30=6.96+0.12) but not SNAP- or SNP-induced relaxation. 5 Superoxide dismutase (SOD), MnCl2, diphenileneiodonium and exposing the luminal surface of the rings outwards (inversion) potentiated the relaxant responses of NO (pIC30=8.52+0.16, 8.23+0.11, 8.01+0.11 and 8.20+0.10, respectively). However, SOD did not modify the NO detected by the electrode and had no e ect on SNAP- or SNP-induced relaxation. 6 Therefore, the kinetics and local distribution of NO release of NO donors in¯uence the susceptibility to the scavenging e ects of oxyhaemoglobin and superoxide. British Journal of Pharmacology (2001) 133, 615 ± 624 Keywords: Sodium nitroprusside; NO; SNAP; superoxide; oxidative stress; pulmonary artery; piglet Abbreviations: DETCA, diethyldithiocarbamate; DPI, diphenileneiodonium; HX, hipoxanthine; iNO, inhaled nitric oxide; L NAME, No-nitro-L-arginine methylester, NO, nitric oxide; ODQ, 1H-[1,2,4]oxadiazolo[4,3-a]quinoxalin-1-one; PPHN, persistent pulmonary hypertension of the newborn; SERCA, sarcoplasmic reticulum Ca2+ ATPase; sGC, soluble guanylate cyclase; SOD, superoxide dismutase; SNAP, S-nitroso-N-acetyl-penicillamine; SNP, sodium nitroprusside; U46619, 9,11-dideoxy-11a,9a-epoxymethano-prostaglandin F2a; XO, xanthine oxidase